Pengalaman Ibu terhadap Perawatan Berkelanjutan (Continuity of Care ) Selama Kehamilan dan Masa Nifas : Studi Kualitatif - Arniyati; Nena Meo , Maria Lupita; Nisa, Khairun (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2025)
Background: Continuity of care is a healthcare approach aimed at providing coordinated, continuous, and holistic care to patients throughout all stages of treatment. The low coverage of antenatal and postnatal visits at Puskesmas, which has not met the national standard target, highlights the need to explore mothers' experiences regarding service quality and continuity of care. Objective: This study aims to explore mothers' experiences with continuity of care during pregnancy and the postpartum period. Method: This qualitative study employed a descriptive phenomenological approach. Data were collected through in-depth interviews involving 10 primary informants and 2 supporting informants, with purposive sampling and content analysis. Source triangulation and member checking were also applied. Results: Three main themes emerged from mothers' experiences: access and barriers to maternal health services, service quality and relationships with healthcare workers, and expectations and benefits of health check-ups. Conclusion: While Posyandu is more accessible, Puskesmas plays a crucial role in follow-up care. Key barriers include transportation and financial issues, though family support is vital. While medical service quality is generally good, administrative services at the registration counter need improvement. Regular evaluations of Puskesmas service quality are necessary to improve access and maternal healthcare services.